IJCM_392A: Assessment of the level of Physical activity among school and college going adolescents in the urban field practice area of Guntur Medical College - Rani Penumaka Sushma; Tulasi P. Naga; Rama A. Sita (Wolters Kluwer Medknow Publications, 2024)
Background: Inadequate Physical Activity is a common feature running through most public health problems across the world. Physical activity declines during the lifespan, especially during adolescence. Identifying patterns of physical activity behaviour in adolescent population will help to improve interventions for youth to become and stay active into adulthood. Objective: 1. To assess the level of physical activity among school and college going adolescents in the urban field practice area of Guntur Medical College. 2. To identify the factors influencing the level of physical activity. Methodology: This cross-sectional descriptive study was carried out among 300 adolescents (aged 10 to 19 years) attending government schools or junior colleges. One school and one college from the field practice area were selected by simple random sampling whereas students from each class were selected by stratified random sampling. A pre-tested, pre-designed semi-structured questionnaire adapted from the Global Physical Activity Questionnaire (GPAQ) and the Physical Activity Questionnaire- Adolescent (PAQ-A) was used for collecting data on physical activity. Results: 30.3% of the adolescents were practicing low physical activity. Level of physical activity was significantly associated with gender, academic grade, father's schooling, availability of facilities in the neighbourhood, and availability of facilities at home. Among adolescents who are practicing low physical activity, 76.1% reported lack of time as the barrier. Conclusion: A substantial proportion of the adolescents are practicing low physical activity varying across different factors viz., gender, academic grade, availability of facilities in neighborhood or at home.